Oviposition capacity and egg mass to fecundity weight ratios in laboratory cultured amblyoma variegatum fabricius, 1794 (Acari: Ixodida) - Nkegbe, E.; Beyuo, J.; Amafu-Dey, H. (Scientific Journal of Zoology, 2014)
We studied the reproductive characteristics of femaleAmblyoma variegatum in the laboratory. These included variations in engorgedweight, percentage body mass due to eggs, and quantity of eggs an engorgedfemale could lay. The results showed that different volumes of blood mealswould be consumed by the same progeny of Am. variegatum female ticks leading todifferent engorged weights. The study revealed that in Am. variegatum egg masscould account for as high as 51% of the engorged body weight. The female tickcould also oviposit as high as 31,487 eggs and also as low as 2421 eggs in samestudy cohorts. The study also showed that the actual engorged weight might notreflect the actual ovipositing capacity of the tick. Only the weight of the eggmass laid determined the actual quantity of eggs.